Getting science wrong : why the philosophy of science matters - Dicken, Paul, 1980- (Bloomsbury Academic, 2018)
Discusses some of the most popular misconceptions about science, and their continuing role in the public imagination. Drawing upon the history and philosophy of science it challenges widespread assumptions and misunderstandings, from creationism and climate change to the use of statistics and computer modeling. The result is an engaging introduction to contentious issues in the philosophy of science and a new way of looking at the role of science in society.